(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Agnikarma is one of the important Para-surgical procedures described in Ayurveda, which has been widely used in the clinical practice now days. Sushruta has given detail description about Agnikarma. Superiority of Agnikarma over other the treatment modalities are timely described by our ancienter because of its Apunrabhavatva i.e., no recurrence property. Pain (Ruja) is the cardinal feature of most of the musculoskeletal disorders and it can affect the quality of life. In modern lifestyle, patient needs instant relief from pain. Treatment available in modern medicine commonly NSAID’s (Nonsteroidal anti-inflammatory drugs) but it has some hazardous effects on body. This review is an attempt has been made to study various research article, analyzed the role of Agnikarma and its applicability on various painful disorders which help to gain best knowledge about Agnikarma. In this article total 15 research works from various journals have been studied conducted on Agnikarma. Agnikarma was found very important tool in pain management of many musculoskeletal disorders. It was found safe, easy, cost-effective and OPD level procedure.